Comment furent rapatriés les greffes de Saint-Domingue, 1803-1820 - Menier, Marie-Antoinette (Gazette des archives, 1978)
The Section Outre-Mer of the Archives nationales keeps some copies of the archives of the tribunals of Saint-Domingue under the French rule. How these copies came to France is a matter of conjecture. Despite many losses, they are of great interest for the history of French Saint-Domingue, because the archives which were left in the island have been nearly ail destroyed.

Les sources de l’histoire des Antilles dans les Archives nationales françaises - Menier, Marie-Antoinette (Bulletin de la Société d'Histoire de la Guadeloupe, 1978)